The relationships between local muscular endurance and kinematic changes during a run to exhaustion at vVO2max - Hayes, P. R.; Bowen, S. J.; Davies, E. J. (The Journal of Strength and Conditioning Research, 2004)
A recent study suggested that runners who maintain a stable running style are able to run for longer at vVO2max velocity (vVO2max). This may be because of the capacity of various muscle groups to maintain their functions despite the onset of fatigue. The purpose of this study was to examine the relationship between local muscular endurance of both the hip and knee extensor and flexor muscle groups and the kinematic changes during a run to exhaustion at vVO2max. Six subelite runners (age 24.2 ± 4.2) participated in this study; they were considered as a homogeneous group based upon their vVO2max scores (coeffeicient of variation = 3.9%). They performed an incremental protocol to determine vVO2max, a series of isokinetic tests to determine the local muscular endurance of both knee and hip flexors and extensors, and a run to exhaustion at vVO2max. The change in kinematic variables between the beginning and the end of the run were correlated with the measures of muscular endurance. Several statistically significant negative correlations emerged between the change in stride length and concentric hip extension (HEcon), r = -0.934; eccentric hip extension (HEecc), r = -0.818; eccentric knee flexion (KFecc), r = -0.957; and change in maximum hip extension (? max HE), r = -0.857; and ? max HE with HEcon, r = -0.846. We concluded that the local muscular endurance of both HEcon and KFecc are important in maintaining a stable running style.